Adaptation of the Pivotal-Differential Genome Pattern for the Induction of Intergenomic Chromosome Recombination in Hybrids of Synthetic Amphidiploids within Triticeae Tribe - Kwiatek, Michal T.; Majka, Joanna; Majka, Maciej; Belter, Jolanta; Wisniewska, Halina (Frontiers in Plant Science, 2017)
A pivotal-differential evolution pattern is when two allopolyploids share a common genome, which is called pivotal, and differ with respect to the other genome or genomes, called differential. This feature induces the intergenomic recombination between chromosomes of differential genomes, which can lead to speciation. Our study is a cytomolecular insight into this mechanism which was adapted for the induction of intergenomic chromosome recombination in hybrids of synthetic amphidiploids Aegilops biuncialis × S. cereale (UUMMRR) and triticale (AABBRR) where R-genome was pivotal. We observed chromosome recombination events which were induced by both: (1) random chromosome fragmentation and non-homologous chromosome end joining at mitosis of root meristem cells and (2) intergenomic chromosome associations at meiosis of pollen mother cells (PMCs) of F1 hybrids. Reciprocal chromosome translocations were identified in six F1 plants and 15 plants of F2 generation using fluorescence in situ hybridization (FISH) with DNA clones (pTa-86, pTa-k374, pTa-465, pTa-535, pTa-k566 and pTa-713). We observed signals of pTa-86, pTa-535 and pTa-k566 probes in several chromosome breakpoints. The comparison of the DNA clone sequences distinguished a number of common motifs, which can be considered as characteristics of chromosome breakpoint loci. Immunodetection of synaptonemal complex proteins and genomic in situ hybridization analysis at meiosis of PMCs of F1 hybrids showed, that the homologous pairing of pivotal R - genome chromosomes is crucial for the fertility of F1 hybrids, however, these chromosomes can be also involved in the intergeneric recombination.